ON LINGUISTIC IDENTITY STATUS AS AN ETHNOLINGUISTIC PHENOMENON IN THE EPOCH OF LANGUAGE CONTACTS - S. V. Pakharenko (Гуманитарные и юридические исследования)
The article studies the current state of the secondary linguistic identity of the Russian within broad language contacts. The main points of formation of secondary linguistic identity are given; spheres of borrowings usage are specified, as well as the quantitative index of borrowings used in these spheres is presented.